FIDELITY ANALYSIS OF THE IMPLEMENTATION OF THE FIQH CURRICULUM IN LEARNING AT MTS. TARBIYATUT THOLABAH - Berlia Putri, Mega; Aniqoh, Durrotun (Program Studi Pendidikan Agama Islam (PAI) Fakultas Tarbiyah dam Ilmu Keguruan Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH) Lamongan, 2025)
This study analyzes the fidelity of the implementation of the Islamic Jurisprudence (Fiqh) curriculum by examining the alignment between lesson plans and classroom practices at MTs Tarbiyatut Tholabah. Unlike previous studies, which generally focus on learning outcomes or the effectiveness of learning methods, this research's novelty lies in the use of the Fidelity of Implementation (FOI) framework to systematically examine the gap between the written curriculum and the actual curriculum in the context of Islamic education, particularly in the subject of Fiqh, which is still relatively rarely studied. This study employed a qualitative approach with field studies. Data were collected through lesson observations, interviews with subject teachers, and analysis of lesson planning documents (lesson plans and teaching modules). Data analysis was conducted thematically and quantitatively-descriptively, referring to the FOI framework, which encompasses the dimensions of adherence to planning, quality of delivery, and consistency of implementation, operationalized through indicators of objectives, materials, methods, media, and learning assessments. Data from observations, interviews, and documents were triangulated to ensure the validity of the findings. The results of the study indicate that the overall fidelity of the Fiqh curriculum implementation is high, particularly in terms of learning objectives, materials, methods, and assessment. Teachers demonstrate consistency in translating planning into contextual and adaptive learning practices. However, the use of instructional media falls into the medium fidelity category, due to limited time allocation and structural learning factors.The medium media fidelity finding indicates that successful curriculum implementation is determined not only by teacher competence but also by organizational support and learning policies. Practically, the results of this study imply the need to strengthen teacher mentoring policies, manage learning time more flexibly, and develop simple and contextual learning media to sustainably improve the fidelity of the Fiqh curriculum implementation